Jasmonate regulates seed dormancy in wheat via modulating the balance between gibberellin and abscisic acid. (1st February 2022) - Nguyen, Tran-Nguyen; Tuan, Pham Anh; Ayele, Belay T
Abstract: Jasmonate (JA) regulates seed dormancy and germination; however, the underlying mechanisms remain poorly understood. Furthermore, it is unclear if JA is an essential regulator of dormancy and germination. We investigated whether the role of JA in regulating seed dormancy in wheat ( Triticum aestivum L.) is mediated by modulation of gibberellin (GA)/abscisic acid (ABA) balance and if the reciprocal modulation of JA level and sensitivity is required for GA-mediated dormancy loss using physiological, pharmacological, and targeted transcriptomic and metabolomic approaches. JA-induced dormancy release in wheat seeds was associated with no change in GA level but up-regulation of GA signaling and ABA catabolism genes, and reduction of the ABA level. Although JA did not affect the expression levels of ABA signaling genes, up-regulation of germination-associated genes indicates a contribution of reduced ABA sensitivity to dormancy release. After-ripening-mediated dormancy loss was also associated with JA–GA synergistic and JA–ABA antagonistic interplays. The prevalence of no effect of GA, which effectively broke dormancy, on the JA-Ile level and expression patterns of JA biosynthesis/signaling and responsive genes reflects that GA-mediated dormancy release occurs independently of JA. Our study concludes that JA induces seed dormancy release in wheat via modulating ABA/GA balance; however, JA is not an essential regulator of dormancy and germination. Abstract : Jasmonate induces seed dormancy release and germination in wheat seeds through enhancing gibberellin sensitivity, and repressing the abscisic acid level and sensitivity. Dormancy release by gibberellin does not require jasmonate.